HUBUNGAN TINGKAT PENDIDIKAN IBU DAN TINGKAT PENDAPATAN KELUARGA DENGAN STATUS GIZI ANAK PRASEKOLAH DAN SEKOLAH DASAR DI KECAMATAN GODEAN - Astuti, Fardhiasih Dwi; Sulistyowati, Taurina Fitriya (Jurnal Kesehatan Masyarakat (Journal of Public Health), 2013)
Background : Based on rank human development index (HDI), Indonesia is on order 109 of state, 174 far below the other asean countries. Factors dominated HDI developed by united nations development program (UNDP) is education, health, and economics. The third factor is very close to nutrition status of society. Based on the research basic health 2010, prevalence toddlers undernourishment ( weight less ) by 18.0 percents 4.9 percent with malnutrition and prevalence toddlers bony ( wasting ) is 13.3 percent. Riskesdas 2010 described inhabitant of consuming food under 70 % of figure adequate nutrition that is recommended 2004 as many as 40,6 percent this situation many units which on a school-age child ( 41.2 % ), adolescent ( 54.5 % ), and pregnant women ( 44.2 % ), this will affect nutrition status. Methods : This research was using crosssectional design. Results : Obtained the status malnutrition 14.5 %, normal nutrition status 82,6 % and nutrition status more 2.9 %. Relation nutrition status with the level of education mother p-value 0,471, relation nutrition status with income p value 0,136 . Conclusion : These were no relationship between nutrition status and the level of education mother, and no relationship between nutrition status with income.   Keyword: education, income, nutrition status